EFFECTS OF BOND’S INTEREST RATE, RATING AND MATURITY TIME TOWARD BOND’S YIELDS - Ayu Mega; Widayat Widayat (Manajemen Bisnis, 2019)
This study aims to determine the effect of interest rates, bond rate, and the maturity time of bond yields on property and real estate companies listed on the Indonesia Stock Exchange in 2013-2018. This type of research is in the form of associative and using a quantitative approach. The research population is property and real estate companies and sampling technique using purposive sampling. Based on the current criteria obtained, 13 companies and 38 bonds that became the research sample. Data analysis technique using Multiple Linear Regression Analysis. The partial test result shows that the variable interest rate and maturity time is positive and significant, while the variable rating bond is negative and significant. The simultaneous test result indicates that the variable of interest rate, bond rating, and maturity time influence simultaneously to the bond yield.